Quantitative label‐free optical technique to analyze the ultrastructure changes and spatiotemporal relationship of enamel induced by Msx2 deletion. Issue 10 (18th July 2021) - Liu, Hao; Guo, Zhouyi; Mo, Luoqi; Sun, Yan; Zhang, JuanJuan; Liu, Xiaoying; Liu, Zhiming
Abstract: New advances in the molecular mechanism of enamel mineralization reveal the practical significance of regenerative medicine in clinical transformation. Muscle segment homeobox 2 (MSX2), a transcription factor, is recently reported to be closely associated with the amelogenesis imperfecta (AI). To elucidate the biomineralization framework of AI enamel, herein, Msx2 gene mutant mice are investigated by dual‐mode noninvasive spectroscopic analytical techniques for the first time. Optical coherence tomography (OCT) records the depth‐resolved structural information of mice teeth, where a dramatic decrease in enamel thickness and quality occurred in Msx2 deficient ( Msx2 −/− ) enamel. And it has the advantages of fast, noninvasive and low cost. Raman spectroscopy, a powerful molecular fingerprint tool, further witnesses an imbalance of inorganic and organic contents in Msx2 −/− enamel. In addition, abnormal expression of MSX2 also influences the spatial distribution of phosphate in enamel according to the Raman spectral imaging. Therefore, OCT integrated with Raman spectroscopy provides the quantitative label‐free optical parameters of both the physical structure and chemical component in mice enamel, which strengthens the understanding of the biomineralization process underlying the Msx2 ‐related amelogenesis imperfect. Abstract : It is the first time that the structural difference of enamel mineralization imperfecta induced by gene defect was found by Raman spectroscopy and optical coherence tomography. And further improved the evaluation criteria of Raman spectroscopy and optical coherence tomography for biomineralization. Revealing the spatiotemporal difference of enamel mineralization caused by Msx2 gene knockout. This study proposes a set of optical analysis methods to solve the problem of enamel mineralization.